Taxonomical Diversity, Socioeconomic and Ethnomedicinal Significance of Bambusa Schreber 1789 (Poaceae: Bambusoideae) in Forest Research Institute (FRI), Dehradun (Uttarakhand), India - Kumar, Mukesh; Upadhyay, Sushil Kumar; Kaur, Harsimran; Verma, Rakesh; Negi, Ranjana; Sharma, Indu; Singh, Raj (Asian Journal of Biological and Life Sciences)
Bamboo is a renewable and versatile resource, characterized by high strength and low weight, and is easily worked using simple tools. It is widely recognized as one of the most important non-timber forest resources due to the high socio-economic benefits from bamboo based products. Bamboo is the world’s fastest growing woody plants with more than three times faster growth. There are about 100 genera and more than 1642 species of bamboo all over the world. In India there are 20 genera and 25 species documented so far. Bamboos are the members of the natural subfamily Bambusoideae, family Poaceae (grass family) under the class Monocotyledonae. Bamboos (the Giant members of the Grass family) are geographically distributed in the tropical and subtropical regions of the world with tall, erect and woody arborescent habits. The present study carried out in the New Forest, Forest Research Institute (FRI), Dehradun (Uttarkhand), India which have immense diversity in genus Bambusa Schreber. Sum of 10 species of Bambusa Schreber were recorded during investigations. The socioeconomic and ethnomedicinal survey reflected that, these contain antibacterial, anticancer and other profound pharmacological properties to cure several diseases. The largest culm sheath was observed in Bambusa bambos (12-30cm), while the smallest culm sheath in Bambusa multiplex (4-5cm). The present study will be an elementary platform to glimpse the wild and cultivated diversity with socioeconomic value of bamboo from a single geographical locality.
Keywords: Bamboo; Bambusa sp.; Culm sheath; ethnomedicine; FRI; New Forest; Poaceae; Socioeconomic; Taxonomical diversity